PENGARUH PENGUNGKAPAN EMISI KARBON, KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Salsa Khairunisa salsa; Hotman Tohir pohan (Jurnal Ekonomi Trisakti, 2022)
The purpose of this research is to analyze the direct and indirect effects of carbon emissions disclosure, environmental performance and Environmental Cost on the company's financial performance. The population of this study is companies listed on the Stock Exchange in 2017 - 2020. The sample in this study werw 92 companies with a purposive sampling method. The types of data in this study are secondary data in the form sustainability reports, annual reports and financial reports contained on the Indonesia Stock Exchange website www.idx.co.id and related to the Corporate Performance Rating (PROPER) Program for 2017-2020 . The results show that Environmental Cost not been approved against ROS, environmental performance and carbon emissions disclosure against ROS